Evaluasi Produktivitas Domba Ekor Gemuk Berdasar Reproductive Rate - Prastowo, Sigit (Caraka Tani: Journal of Sustainable Agriculture, 2005)
Fat Tailed Sheep represent one of Indonesian livestock that having excellence of comparability with other ruminants livestock. The excellence is quickly adult, short of pregnant age, and has the nature of bearing twin, so if evaluated from development aspect will be very beneficial. Reproductive Rate (RR) is a mount of reproduction ability from a group of ewes. Reproductive Rate defined as amount of weaned lamb by ewe every year. Variable/component related to RR are litter size, lamb mortalities before weaning and lambing interval.Litter size is general influenced by difference of breeds, age and sufficiency of nutrition. Litter size is peculiarly influenced by ovulation rate that determined by breed, age, nutrition and parity. Lamb age, litter size, birth weight, season, nutrition and parity are influenced lamb mortalities before weaning. Lambing interval determined by nutrition factor and management, which is matting pattern and lamb weaning.